Generalised Diameter-Height Equations for Even-Aged Stands of Azadirachta indica in Gujarat State of India - Tewari, V. P. (Indian Forester, 2006)
The objective of this study was to develop and compare some generalised diameter-height equations for pure stands of neem (Azadirachta indica A. Juss) in semi-arid region of Gujarat State in India. The data used to fit the equations consisted of 761 diameter-height observations collected from the plots laid out in pure, uniformly stocked stands of varying age and density. Non-linear least squares regression was applied to test the performance of four published equations and the performance of these equations was evaluated using different statistical criteria. Finally, these equations were applied on an independent data set for validation purpose. The equation 1 (Pienaar function) which performed poorly during fitting phase was found to perform best in validation phase when applied to independent data set. This contrasting result emphasises the necessity of model validation as an important step in model construction process. Overall, equation 4 (Hui and Gadow function) was found to perform satisfactorily for both the fitting data set as well as validating data set.